2018
DOI: 10.1111/cas.13610
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathogenesis of pancreatic ductal adenocarcinoma: Impact of passenger strand of pre‐miR‐148a on gene regulation

Abstract: We previously used RNA sequencing to establish the microRNA (miRNA) expression signature of pancreatic ductal adenocarcinoma (PDAC). We found that both strands of pre‐miR‐148a (miR‐148a‐5p: the passenger strand and miR‐148a‐3p: the guide strand) were downregulated in cancer tissues. Ectopic expression of miR‐148a‐5p and miR‐148a‐3p significantly inhibited cancer cell migration and invasion, indicating that both strands of pre‐miR‐148a had tumor‐suppressive roles in PDAC cells. In silico database and genome‐wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 49 publications
1
45
0
2
Order By: Relevance
“…Contrary to this theory, recent studies have shown that some miRNA passenger strands have tumor-suppressive functions, and their target genes can contribute to cancer progression, metastasis, and drug resistance in several types of cancers [ 18 , 19 , 20 , 21 , 22 , 23 ]. Our recent studies of PDAC cells revealed that miR-216a-3p , miR-216b-3p, miR-148a-5p, and miR-130b-5p were significantly downregulated in PDAC tissues using our RNA-sequencing based signature expression patterns [ 24 , 32 , 33 ]. Ectopic expression assays demonstrated that their expression attenuated the malignant phenotypes of PDAC cells and that the genes they regulate were aberrantly expressed in PDAC clinical specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this theory, recent studies have shown that some miRNA passenger strands have tumor-suppressive functions, and their target genes can contribute to cancer progression, metastasis, and drug resistance in several types of cancers [ 18 , 19 , 20 , 21 , 22 , 23 ]. Our recent studies of PDAC cells revealed that miR-216a-3p , miR-216b-3p, miR-148a-5p, and miR-130b-5p were significantly downregulated in PDAC tissues using our RNA-sequencing based signature expression patterns [ 24 , 32 , 33 ]. Ectopic expression assays demonstrated that their expression attenuated the malignant phenotypes of PDAC cells and that the genes they regulate were aberrantly expressed in PDAC clinical specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of the miRNA expression signatures demonstrated that certain miRNA passenger strands were downregulated and acted as antitumor miRNAs in several cancers, e.g., miR-145-3p, miR-150-3p, miR-148a-5p and miR-99a-3p (20,24,35,36). Our previous studies demonstrated that antitumor miR-145-3p directly targeted oncogenes, e.g., MTDH in lung adenocarcinoma, UHRF1 in bladder cancer, MYO1B in head and neck cancer and MELK, NCAPG, BUB1 and CDK1 in prostate cancer (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs serve roles in numerous physiological and pathological processes including apoptosis, the cell cycle, cellular growth, proliferation, differentiation, metabolism and aging (6). Accumulating evidence reveals that miRNA dysfunction influences the metastasis, chemo-radioresistance and overall survival time of patients with cancer, including patients with PDAC (7)(8)(9)(10). Previous reports have revealed miRNA involvement in PDAC progression, including roles of miR-216b (11), miR-10a-5p (10), miR-374b-5p (12), miR-1271 (13), miR-7-5p (14), miR-4295 (15) and miR-185 (16).…”
Section: Introductionmentioning
confidence: 99%